Managerial Ownership as A Selective Moderator: Strengthening the Role of Capital Structure and Profitability in Firm Value - Moh. Cholid Mawardi; Anik Malikah (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2025)
This study investigates the influence of capital structure, profitability, and firm size on firm value with managerial ownership as a moderating variable. The analysis is based on secondary data from 78 consumer goods companies listed on the Indonesia Stock Exchange during 2020–2022, producing 234 observations tested using Moderated Regression Analysis (MRA). The results show that capital structure (DER) has a significant positive effect on firm value, while profitability (ROA) and firm size have no significant effect. Profitability does not influence firm value due to unstable earnings during the COVID-19 period, and firm size is also irrelevant since large assets do not always generate profits. Managerial ownership, however, is found to strengthen the effects of capital structure and profitability on firm value but does not moderate the effect of firm size, as asset growth without profitability provides little assurance to investors and managerial shareholding in these companies remains relatively small. The novelty of this study lies in demonstrating that managerial ownership acts as a selective moderator, reinforcing some relationships while failing to affect others, thereby offering new insight into ownership structures and firm value in emerging markets.Keywords: capital structure, profitability, firm size, managerial ownership, firm value